Adaptive Structuration within Isomorphism in Strengthening BKPSDM of Southwest Papua Province - Ignatius Randhy Frieder; Badu Ahmad; Muh. Akmal Ibrahim; Didik Iskandar (CV. Doki Course and Training, 2026)
Adopting national structures, systems, and procedures does not automatically yield institutional effectiveness; what matters is the process of appropriation and adaptation by organizational actors, which becomes critical under the constraints of an affirmation setting. This study analyzes adaptive structuration across three dimensions—structure as rules and resources, the duality of structure and agency, and appropriation and adaptation—in the adoption of personnel systems and procedures at BKPSDM of Southwest Papua Province. An interpretive qualitative case-study design was used, relying on in-depth interviews, observation, and documentation, analyzed with the interactive model of Miles, Huberman, and Saldaña under Adaptive Structuration Theory. Rules, resources, systems, and procedures are complete on paper but not yet meaningful in practice; officials’ capacity to interpret, negotiate, and modify national provisions is low, so they tend to receive structure passively; and appropriation stops at the procedural level and is often misaligned with the systems’ original intent. The study yields a typology of adaptation—procedural, pragmatic, and substantive. The three dimensions form a chain that breaks in the middle because the agency dimension is weak, so the adaptation that forms is dominated by the symbolic type; weak agency is the decisive link, while the typology becomes a basis for practice-based institutional-maturity measurement